Propedeutyka rozumienia godności człowieka - Ziombra, Andrzej (Społeczeństwo, 2024)
How should human dignity be properly understood? It seems that personalistic anthropology speaks most fully about human dignity. It perceives a human being as an entity with spiritual and material qualities, living in a community of other persons who possess the same qualities. From this perspective, one sees a person who, in experiencing their own dignity, takes into account the dignity of others. This way, it is possible to avoid the dangerous tendency towards a divergence between the absolutization of dignity and the relativization of human life.